2020
DOI: 10.1101/2020.06.08.140798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation of an α-synuclein liquid droplet state and its maturation into Lewy body-like assemblies

Abstract: Misfolded a-synuclein is a major component of Lewy bodies, which are a hallmark of Parkinson's disease. A large body of evidence shows that a-synuclein can self-assemble into amyloid fibrils, but the relationship between amyloid formation and Lewy body formation still remains unclear. Here we show, both in vitro and in a C. elegans model of Parkinson's disease, that a-synuclein undergoes liquid-liquid phase separation by forming a liquid droplet state, which converts into an amyloid-rich hydrogel. This maturat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 72 publications
5
54
0
Order By: Relevance
“…With the aim of elucidating if homogeneous primary nucleation and thus the formation of antiparallel -sheet aggregates can be triggered inside αS droplets generated by LLPS, we have reproduced the conditions of reported in vitro αS droplet formation 68 and observed aggregation inside the droplets very rapidly (within 2h of incubation, not shown) ( Fig. 8B), with essentially all the protein being aggregated in less than 20 h (Fig.…”
Section: Antiparallel -Sheet Aggregates Represent the Most Stable Stsupporting
confidence: 57%
See 1 more Smart Citation
“…With the aim of elucidating if homogeneous primary nucleation and thus the formation of antiparallel -sheet aggregates can be triggered inside αS droplets generated by LLPS, we have reproduced the conditions of reported in vitro αS droplet formation 68 and observed aggregation inside the droplets very rapidly (within 2h of incubation, not shown) ( Fig. 8B), with essentially all the protein being aggregated in less than 20 h (Fig.…”
Section: Antiparallel -Sheet Aggregates Represent the Most Stable Stsupporting
confidence: 57%
“…Indeed, recent experimental evidences suggest a role of these protein droplets on the in vivo aggregation of these amyloidogenic proteins and the induction of pathology 66 . Very recently, it has been reported that αS droplet formation by LLPS precedes its aggregation in cellular 67 and animal models 68 and the liquid-to-solid transition of αS droplets has been recapitulated in vitro.…”
Section: Antiparallel -Sheet Aggregates Represent the Most Stable Stmentioning
confidence: 99%
“…We applied the FuzDrop method to predict the droplet-promoting propensities of two proteins reported to undergo liquid-liquid phase separation, TDP-43 (37) and a-synuclein (38,39). Our results indicate that the low-complexity (LC) region of TDP-43 (residues 262-414) mediates spontaneous phase separation.…”
Section: Droplet-promoting Propensity Profiles Of Tdp-43 and A-synucleinmentioning
confidence: 99%
“…One of the cellular microenvironments with a particularly low content of water (by definition) is the interior of protein-rich droplets, generated by liquid-liquid phase separation (LLPS). These phase separated protein droplets likely play a role in the in vivo aggregation of a number of amyloidogenic proteins such as tau [104,105], TDP-43 [106,107] and αS [108,109]. Although the mechanism of the liquid-to-solid transition of these protein droplets is unclear, our recent data on the amyloid aggregation inside αS droplets generated in vitro suggest that the process is triggered by homogeneous primary nucleation resulting in the formation of amyloid aggregates with a preference for an intermolecular antiparallel β-sheet structure [92].…”
Section: Primary Nucleationmentioning
confidence: 99%
“…Water activity and, therefore, the protein hydration state have been recently demonstrated to be a key determinant not only for triggering αS self-assembly (maintaining αS monomeric and preventing it from misfolding and self-assembly under highly hydration conditions), but also for dictating the preference for the type of primary nucleation (heterogeneous vs homogeneous) and the type of structural amyloid polymorph generated (parallel vs antiparallel β-sheet structure). Conditions of very poor water activity such as those encountered inside protein-rich droplets, generated by LLPS, have been reported to be particularly efficient in triggering αS amyloid aggregation both in vitro and in vivo [105,108,109].…”
Section: Physicochemical Factors Affecting Amyloid Aggregation Processmentioning
confidence: 99%